1985
DOI: 10.1080/00071668508416827
|View full text |Cite
|
Sign up to set email alerts
|

Influence of energy intake on growth and utilisation of dietary protein and energy in germ‐free and conventional chicks

Abstract: The effect of metabolisable energy (ME) intake on the growth and utilisation of dietary protein and energy in germ-free (GF) and conventional (CV) chicks was investigated in two experiments. In experiment 1 a high energy diet (HED, 14.8 kJ ME/g) and a marginally-adequate energy diet (AED, 11.7 kJ ME/g) were fed to the GF and CV chicks at 240 g/2 birds/10 d. In experiment 2 a diet with 13.7 kJ ME/g was fed at 118 g (low level, LL) or 128 g (high level, HL)/bird/10 d. Body weight gain, protein retention and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…The use of an iso protein diet in our study may have increased ME/CP ratio of the diets, and this change may have caused excess abdominal fat in ducks, which was supported by Scott et al (1959), who observed that the carcass fat of 7.5-wk-old Pekin ducks increased as dietary ME/CP ratio increased. Furthermore, more fat deposition caused by high-energy diets may be due to higher efficiency of energy retention at this instance, and similar results in broilers were reported by Jackson et al (1982b) and Furuse et al (1985). Boekholt et al (1994) also found that the efficiency of energy retention was higher in fat than in protein when high-energy diets were consumed by broilers.…”
Section: Resultssupporting
confidence: 83%
“…The use of an iso protein diet in our study may have increased ME/CP ratio of the diets, and this change may have caused excess abdominal fat in ducks, which was supported by Scott et al (1959), who observed that the carcass fat of 7.5-wk-old Pekin ducks increased as dietary ME/CP ratio increased. Furthermore, more fat deposition caused by high-energy diets may be due to higher efficiency of energy retention at this instance, and similar results in broilers were reported by Jackson et al (1982b) and Furuse et al (1985). Boekholt et al (1994) also found that the efficiency of energy retention was higher in fat than in protein when high-energy diets were consumed by broilers.…”
Section: Resultssupporting
confidence: 83%
“…The previous explanation is supported by results of Scott et al (1959). Furthermore, more fat deposition caused by high-energy diets may be due to higher efficiency of energy retention at this instance, similar results in broilers were reported by Jackson et al(1982) and Furuse et al (1985). Moreover, Boekholt et al (1994) found that the efficiency of energy retention was higher in fat than in protein when high energy diets were consumed by broilers.…”
Section: Some Carcass Traits: Effect Of Energy Levelsupporting
confidence: 83%
“…Unsuitable micro flora population in the gastrointestinal tract will lead to unfavorable nutrient absorption [16] and the increasing energy requirements for maintenance [17]. This may be a possible mechanism for higher growth and better FCR in broiler consuming SEO.…”
Section: Growth Parametersmentioning
confidence: 99%